CONTRACT MARKETING DALAM PEMASARAN BENIH IKAN : STUDI KASUS DI KELOMPOK PEMBUDIDAYA IKAN KECAMATAN KALASAN KABUPATEN SLEMAN - , HENNY PUSPA SARI SIHOMBING ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was held to investigate the model of contract marketing between Fish Farmers Group (KPI) in Sleman Regency and company (PT Aquafarm Nusantara), the factors led to the emerging of contract, and benefit of contract. The study was conducted on two selected groups, KPI Mina Jaya and KPI Mina Soka Makmur. Respondents were 26 people consisting of 17 respondents in KPI Mina Jaya and 9 respondents in KPI Mina Soka Makmur and were interviewed using questionnaire. The results indicate that the model of contract is not a written contract. For fish farmers, the supporting conditions for the emerging of contract were the ability of partner (company) to supply fish larvae, satisfaction in the seed production, guaranteed seed market, acquire additional knowledge about fish farming, guaranteed minimum price and supply of production inputs such as feed and vitamins. Meanwhile, the company also needed fish farmers to ensure the continuing supply of standardized fish seed and reasonable and agreed price. Therefore, the contract offers benefit to KPI in ensuring the continued supply of fish seed, market guarantee, price certainty